Proses Coaching Latsar CPNS di BPSDM Daerah Provinsi Lampung - Aulia, Bunga; Hudalil, Ahmad; Banuwa, Anisa Kuswandari; Wijanarko, Agus (Jurnal Abdimas Multidisiplin, 2025)
Purpose: Describes the coaching of Latsar CPNS at the Regional Human Resources Development Agency of Lampung Province. Research methodology: The research method used in this study is a descriptive with a qualitative approach, where the data collection technique uses observation and interviews with the determination of snowball sampling data sources. Results: The current Coach Latsar CPNS appointment is an assignment; There is no special discussion room in the CPNS Latsar coaching process and there is an understanding of coaching aspects that are not optimal in terms of focus and use of diagnostic tools. Conclusion: The coaching process in the Basic Training for Civil Servant Candidates (Latsar CPNS) at the Regional Human Resource Development Agency of Lampung Province has not yet been fully optimized, as there is no clear guideline on coach qualifications and competencies, limited discussion spaces and supporting facilities, and a lack of formal coaching training for appointed coaches. Limitations: it is necessary to immediately set guidelines which regulate the terms and standards of competence and qualifications of the Latsar CPNS coach; need to be supported by special facilities and infrastructure related to coaching and it is necessary to immediately hold training, explanations and directions on coaching before being assigned as a coach at the CPNS Latsar. Contribution: This study is expected to be used as the recommendation material that can improve the implementation of the training and training for representatives of BPSDMD Lampung Province in the future.